Estrategia EDENFO en la competencia construye su identidad con estudiantes de secundaria en la I.E. N° 60087 Lucille Gagne Pellerin, Santa Clotilde 2022 - Davila Manrique, Nefrit Edith (2023)
In this research we sought to recognize if there is a significant effect of the application of the EDENFO strategy for the improvement in the construction of their identity competence in students who attend the 4th grade A, B, C and D of secondary school in I.E. Nº60087 Lucille Gagne Pellerin, Santa Clotilde in the year 2022, this study was worked in experimental form since a new strategy was applied and designed by the author, and a pre-test was carried out in the first instance through an observation sheet to verify in what conditions the knowledge on the construction of their identity was entered, which gave a result mostly of regular, then twelve (12) learning sessions were carried out during an academic school trimester, which were three (03) calendar months, to then carry out a post-test and collect the final information, which was mostly good, with this information a comparison was made of the observations collected, which were tabulated for a better understanding of the data. The target population were all the students who were studying at the secondary level in the I.E. Nº60087 Lucille Gagne Pellerin de Santa Clotilde, but the sample under study were only the students who were in the 4th grade, in its four (04) sections, finally after making the analysis of the information it was possible to confirm that in effect the application of the EDENFO strategy, produced a positive change in the competence construction of their identity in the students who were part of the sample.